Transformasi Pembelajaran Berbasis Mobile-AI: Persepsi Mahasiswa Terhadap ChatGPT di Era Masyarakat 5.0 - Indriani, Lisa; Samola, Trifena Feisa; Irwansyah (Philosophiamundi, 2025)
Rapid digital transformation has brought significant changes to the world of education, especially in the way students access and process information. One of the innovations in the spotlight is the use of artificial intelligence (AI) technology such as ChatGPT as a learning aid. ChatGPT is present as a Mobile-AI-based communication media that is interactive, flexible, and responsive in helping students understand the material independently. This study aims to determine students' perceptions of the use of ChatGPT in the context of digital communication via mobile devices in the era of society 5.0. This study uses a descriptive qualitative approach with an in-depth interview method with students who actively use ChatGPT in academic activities. The results of the study show that the majority of students have a positive perception of ChatGPT because it is considered to facilitate the learning process, speed up information searches, and support independent learning. However, concerns were also found regarding the accuracy of information, potential dependency, and the importance of digital literacy skills. These findings reveal that Mobile-AI communication, especially through ChatGPT, has formed a new pattern of interaction between students and technology, which is not only instrumental but also influences the way they think and learn. Therefore, the use of ChatGPT needs to be balanced with ethical and reflective awareness so that it can be optimally utilized in digital learning.